2012
DOI: 10.1186/1472-6963-12-275
|View full text |Cite
|
Sign up to set email alerts
|

A 10 year (2000–2010) systematic review of interventions to improve quality of care in hospitals

Abstract: BackgroundAgainst a backdrop of rising healthcare costs, variability in care provision and an increased emphasis on patient satisfaction, the need for effective interventions to improve quality of care has come to the fore. This is the first ten year (2000–2010) systematic review of interventions which sought to improve quality of care in a hospital setting. This review moves beyond a broad assessment of outcome significance levels and makes recommendations for future effective and accessible interventions.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 33 publications
0
45
0
Order By: Relevance
“…Literature relating to quality of care in family planning services found that a number of approaches have been used to define and measure quality of care in family planning services and its determinants, and these vary with the stakeholders’ priorities and perspectives [25]. The Donabedian [26,27] and Bruce Frameworks [28] are the two conceptual frameworks that have been used most frequently since the early 1990s to inform empirical work assessing the quality of family planning services and factors that determine quality of care in family planning services.…”
Section: Introductionmentioning
confidence: 99%
“…Literature relating to quality of care in family planning services found that a number of approaches have been used to define and measure quality of care in family planning services and its determinants, and these vary with the stakeholders’ priorities and perspectives [25]. The Donabedian [26,27] and Bruce Frameworks [28] are the two conceptual frameworks that have been used most frequently since the early 1990s to inform empirical work assessing the quality of family planning services and factors that determine quality of care in family planning services.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, an educational part on safety science (such as the state of affairs, terminology, and examples) was added to the workshop. Education is perceived as important in quality improvement 38 and is the most important factor to improve patient safety in primary care. 39 The aim was to educate staff on safety science providing them with a sense of urgency concerning safety in general practice, in order to instigate change.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…Our review, part of the ORCAB FP7 project (Montgomery et al, 2011;Conry et al, 2012;McGowan et al, 2013), explores the link between organizational culture, healthcare professional burnout and quality. Focusing on quality and staff burnout in the current climate is important because deteriorating working conditions in the health sector threaten service quality and patient safety (Kingma, 2009).…”
mentioning
confidence: 99%